Legal Protection as a Preventive Strategy Against Violence for Female Nurses on the Night Shift - Mohamad Caesar Ramadhani; Muh. Ali Masnun (NOVUM : JURNAL HUKUM, 2025)
The aim of writing this research is to analyze the legal protection for female nurses who are employed at night and to describe the obstacles that may occur in implementing legal protection for female nurses who are employed at night at the Mabarrot Hasyimiyah NU Manyar Clinic, Gresik Regency. This research is empirical legal research, which was carried out by looking at the implementation of law according to conditions in society. Based on an analysis of the laws and regulations in Indonesia which regulate protection for female workers who are employed at night, forms of protection for female workers were found, namely getting nutritious food and drinks, maintaining decency and safety while at work, getting pick-up and drop-off transportation for women. female workers going to and from work, Availability of security guards at the workplace, Availability of proper bathrooms with adequate lighting and separate for female and male workers. Based on the research, it was concluded that there are still several factors such as limited operational funds, lack of workers' understanding of their rights, and lack of supervision and guidance from related agencies which are the main obstacles in implementing legal protection for female nurses who work at night.